Chemical Element Profiles in Commercial Woven Fabric Combining Laser-Induced Breakdown Spectroscopy and Chemometrics - Cardoso Santos, M. [UNESP]; Dai, C. [UNESP]; Manhas Verbi Pereira, F. [UNESP] (Springer Nature, 2018)
High-heterogeneity solid woven fabric samples were investigated using laser-induced breakdown spectroscopy (LIBS) and chemometrics. Many emission lines were relevant to characterize this material at the surface and in deeper layers of fibers. Differences among dyes and fibers were clearly observed. The scores maps showed the possibility of comparing the chemical compositions of the dye and fiber independent of the print of fabric. Variations in the composition were verified by carrying out a pattern for mapping using a sophisticated LIBS system. This screening can provide a fast evaluation of samples and may associate this information with classification, authenticity or even for forensic analysis of fabric materials.
Keywords: chemometrics; laser-induced breakdown spectroscopy; woven fabric